Methods used to investigate tone of pelvic floor muscles in pelvic health conditions: A systematic review - Rachel Worman; Ryan E. Stafford; David Cowley; Paul W. Hodges (Continence, 2023)
Aim:: This study aimed to systematically review which tools and outcome measures have been used to assess increased tone of PFM in pelvic health conditions. Methods:: Databases were searched for papers that studied increased PFM tone in any pelvic health condition. Studies of any design were eligible if they included primary data. Data were extracted regarding measurement types, outcome measures and reference to reliability or validity. Eight measurement types were identified (EMG, dynamometry, manometry, digital palpation, MRI, ultrasound, defecography, and other). Outcome measures were considered with respect to the property measured, the measure’s interpretation, repeatability, validity and measurement issues. Results:: Screening of 7910 papers from the search and review of reference lists identified 151 papers that used 103 outcomes measures from eight measurement tools. Most outcome measures indirectly assessed PFM tone without validation. Repeatability was often acceptable, but many measurements were compromised by application issues that preclude accurate interpretation. EMG, dynamometry and manometry at rest and during tasks in which relaxation is expected had face validity and could be interpreted as increased tone if critical measurement issues were considered/controlled. Conclusion:: This systematic review provides foundation to interpret literature that has assessed increased PFM tone and informs selection of measurement tools and design for future studies.